2017
DOI: 10.1080/17843286.2017.1326547
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure with need for renal replacement therapy as a complication of zoonotic S. zooepidemicus infection: case report and review of the literature

Abstract: Streptococcus zooepidemicus is an animal commensal with the potential of zoonotic transmission through ingestion of contaminated dairy products, leading to outbreaks of Post-Streptococcal Glomerulonephritis (PSGN). We report for the first time acute renal failure with need for renal replacement therapy, as a complication of S. zooepidemicus bacteremia resulting from direct horse to human transmission in a young adult. Both clinical disease course and immunohistochemical staining patterns on renal biopsy had so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…No isolate was recovered in the analyzed milk or cheese samples (4). The sequence described in the current study shared sequence identity with SS1215 APSGN/England/1992 (3) and szp5058-APSGN/ Nova Serrana-MG, Brazil/1998 (22) but not with szp1028 APSGN/Romania 1968 (22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…No isolate was recovered in the analyzed milk or cheese samples (4). The sequence described in the current study shared sequence identity with SS1215 APSGN/England/1992 (3) and szp5058-APSGN/ Nova Serrana-MG, Brazil/1998 (22) but not with szp1028 APSGN/Romania 1968 (22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 52%
“…The isolates were categorized as clonal due to their indistinguishable banding patterns with high similarity (Ͼ99%) by rep-PCR, characterizing the genetic relationship between them and confirming the outbreak. Previous studies reported a milk-borne outbreak with 85 cases of sore throat and, later, APSGN in the town of Piatra Neamt, Romania (1968), where the S. zooepidemicus szpHV3 gene was identified in lymph node biopsy specimens and pharyngeal exudate of patients, in carriers, and in cow milk samples (22)(23)(24)(25)(26)(27). Fifteen years later, another outbreak attributed to S. zooepidemicus HV5 took place in North Yorkshire, England (1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection occurs by eating unpasteurized dairy products, cheese, pork meat or direct contact with horses. The clinical forms described thus far include meningitis, septic arthritis, endocarditis, glomerulonephritis, streptococcal toxic shock syndrome, pneumonia, pharyngitis, lymphadenitis, osteomyelitis, rheumatic fever, and skin and soft tissue infections [68,84,90,91]. Table 6 presents details of selected cases of SEZ infections in humans.…”
Section: Streptococcus Equi Subsp Zooepidemicus (Sez)mentioning
confidence: 99%